Men's Intrusion, Women's Embodiment: A critical analysis of street harassment - Vera-Gray, F. (Routledge, 2018)
Research on violence against women tends to focus on topics such as sexual assault and intimate partner violence, arguably to the detriment of investigating men’s violence and intrusion in women’s everyday lives. The reality and possibility of the routine intrusions women experience from men in public space – from unwanted comments, to flashing, following and frottage – are frequently unaddressed in research, as well as in theoretical and policy-based responses to violence against women. Often at their height during women’s adolescence, such practices are commonly dismissed as trivial, relatively harmless expressions of free speech too subjective to be legislated against. Based on original empirical research, this book is the first of its kind to conduct a feminist phenomenological analysis of the experience for women of men’s stranger intrusions in public spaces. It suggests that intrusion from unknown men is a fundamental factor in how women understand and enact their embodied selfhood. This book is essential reading for academics and students involved in the study of violence against women, feminist philosophy, applied sociology, feminist criminology and gender studies.

“The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Bennett, Toby (IASPM Journal, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.
Keywords: Industrial Reflexivity; Inequalities; KEYWORDS: Creative labour; Major record labels; Post-feminism.

'Shocking' level of sexual harassment at music festivals (BBC News, 2018)
Up to 43% of women under 40, who have been to a music festival, say they have faced unwanted sexual behaviour.

The music business’s gender pay gap is embarrassing and uncomfortable. It’s time for change. (Music Business Worldwide, 2018)
MBW Contributing Editor, Rhian Jones, gives her take on the news…

EDM and Ecstasy: the lived experiences of electronic dance music festival attendees - Little, Noah; Burger, Birgitta; Croucher, Stephen M. (Journal of New Music Research, 2018)
Attendance at large-scale music festivals has captivated a global interest in these spectacular experiences, yet little is known about the lasting benefits and personal changes individuals incur following this event. This study aims to provide a comprehensive exploration of the lived experiences of individuals who attended a multi-day electronic dance music festival. The present study was primarily interested in the perceived beneficial changes within the individual, following their festival experience. We investigated if first-time festival attendees perceived changes differed to those of returning individuals. Semi-structured qualitative interviews were used to collect data from 12 individuals who attended the 2015 Electronic Daisy Carnival in Las Vegas. Six participants were first-time attendees while the remaining six were individuals returning to the festival. The data was analysed using Thematic Analysis. Within the data emerged the following central themes: (1) escape, (2) communitas, and (3) self-reported changes; there were 10 subthemes. These findings add to the existing body of music festival literature, further contextualizing how music festivals are both experienced, and reflected upon by individuals. Further, this study highlights the potential lasting changes individuals’ experience from attending electronic dance music festivals.
Keywords: Music festival; electronic dance music; music; social acceptance; social cohesion

“Essential—Passion for Music”: Affirming, Critiquing, and Practising Passionate Work in Creative Industries - Bennett, Toby (The Palgrave Handbook of Creativity at Work, 2018)
This chapter considers “passion” as an enthusiastic orientation to work within creative worlds: work motivated by intense attachments to the products of work and their conditions of production. Drawing on Luc Boltanski’s pragmatic sociology of critique and justification, the chapter argues that the passionate lens most usefully trains our sights on normative questions: not what or how—but why such work is undertaken. Embedded in research on cultural and creative industries, the contemporary recorded music sector is presented as a “passionate” industry in transformation. Interviews with workers, who both criticize and defend their industry, act as a springboard to explore three possible interpretive approaches: affirmative, critical, and pragmatic. Theoretical flexibility is needed to keep “passion” open to future inquiry—particularly regarding inequalities in creative work.

"I Didn't Want To Be 'That Girl'": The Social Risks of Labeling, Telling, and Reporting Sexual Assault - Khan, Shamus; Hirsch, Jennifer; Wamboldt, Alexander; Mellins, Claude (Sociological Science, 2018)
This article deploys ethnographic data to explain why some students do not label experiences as sexual assault or report those experiences. Using ideas of social risks and productive ambiguities, it argues that not labeling or reporting assault can help students (1) sustain their current identities and allow for several future ones, (2) retain their social relationships and group afﬁliations while maintaining the possibility of developing a wider range of future ones, or (3) avoid derailing their current or future goals within the higher educational setting, or what we call “college projects.” Conceptually, this work advances two areas of sociological research. First, it expands the framework of social risks, or culturally speciﬁc rationales for seemingly illogical behavior, by highlighting the interpersonal and institutional dimensions of such risks. Second, it urges researchers to be more attentive to contexts in which categorical ambiguity or denial is socially productive and to take categorical avoidance seriously as a subject of inquiry. Substantively, this work advances knowledge of why underreporting of campus sexual assault occurs, with implications for institutional policies to support students who have experienced unwanted nonconsensual sex regardless of how those students may label what happened.

Navigating the Margins between Consent and Dissent: Mechanisms of Creative Control and Rock Music in Late Socialist Romania - Mogoș, Petrică; Berkers, Pauwke (East European Politics and Societies: and Cultures, 2018)

The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Toby, Bennett (Gender Politics in the Music Industry, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.